A nickel nanocluster modified porous core-shell composite indium oxide material and its preparation method and application
Modifying the porous core-shell complex phase indium oxide material by nickel nanoclusters, the problems of low sensitivity and slow response recovery of existing NO2 sensors are solved, and transient NO2 detection in high sensitivity, high selectivity and wide concentration range are achieved.
Patent Information
- Application Number
- CN202411325801.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing NO2 sensors have problems such as low sensitivity, high detection limit and slow response recovery. They cannot ensure that the gas-sensitive reaction site is in rapid contact with the NO2 molecules to be tested, and the semiconductor metal oxides have poor reactivity with NO2.
Nickel nanoclusters are used to modify the porous core-shell complex phase indium oxide material. Through its unique porous hollow core-shell morphology structure and the high NO2 catalytic activity of nickel nanoclusters, the diffusion and adsorption process of NO2 molecules are promoted and the surface formation process of chemically adsorbed oxygen is inhibited.
It realizes transient NO2 detection in a high sensitivity, high selectivity and wide concentration range at lower operating temperatures, with excellent practical application value and industrial production prospects.
Smart Images

Figure CN119191341B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas-sensitive materials and relates to a nickel nanocluster-modified porous core-shell composite indium oxide material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Since nitrogen dioxide (NO2) can cause serious environmental problems and threaten human health, it is necessary to detect NO2 gas quickly, quantitatively and accurately. Currently, the most commonly used and widely studied NO2 sensor is the resistive semiconductor metal oxide gas sensor, which works by using the material to exchange electrons with the gas molecules to be measured, causing the energy band of the semiconductor metal oxide material to bend, and the carrier concentration and resistance to change, which then manifests as a response to the gas to be measured. However, in the actual work of NO2 sensors, low sensitivity, high detection limit, and slow response recovery speed are often shown. Traditional semiconductor metal oxide sensors cannot ensure that the gas-sensitive reaction site is in rapid contact with the NO2 molecules to be measured. In addition, the reaction activity of semiconductor metal oxides with NO2 is poor, and the thermodynamic barrier required for gas-sensitive reactions is high. NO2 gas-sensitive reactions require higher operating temperatures and longer response recovery times, which leads to a significant deterioration in the material's gas-sensitive performance to NO2. Summary of the invention
[0004] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a nickel nanocluster modified porous core-shell composite indium oxide material and a preparation method and application thereof. The material provided by the present invention utilizes its unique porous hollow core-shell morphology structure, the high NO2 catalytic activity and surface dispersibility of nickel nanoclusters to significantly promote the diffusion and adsorption process of NO2 molecules, inhibit the surface formation process of chemically adsorbed oxygen, and successfully achieves transient NO2 detection with high sensitivity, high selectivity and a wide concentration range at a relatively low operating temperature, and has excellent practical application value and prospects for industrial production.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] In the first aspect, a nickel nanocluster modified porous core-shell composite indium oxide material comprises indium oxide and metallic nickel, wherein the molar ratio of indium oxide to metallic nickel is 1:(0-0.2);
[0007] The crystal phase of the indium oxide is a composite phase composed of a cubic phase and a rhombic corundum phase, and the structure of the indium oxide is a porous hollow core-shell micron-spherical structure, which is composed of a shell layer wrapping a core, and a hollow cavity is formed between the shell layer and the core, wherein the shell layer is composed of porous indium oxide nanoparticles, and the core is a micron-sphere assembled from porous indium oxide nanoparticles;
[0008] Metallic nickel is dispersed in the form of nanoclusters on the surface of the porous hollow core-shell micron-spherical structure.
[0009] Indium oxide is an n-type semiconductor with high conductivity and narrow band gap. As a matrix of composite materials, it provides the main gas-sensitive reaction sites. The large number of gaps between nanoparticles and between core and shell in the porous hollow core-shell micron-spherical structure provide channels for gas diffusion. The core-shell morphology design significantly increases the specific surface area of the material, providing more gas adsorption sites for gas-sensitive reactions. The composite phase formed by the metastable rhombic corundum phase and the stable cubic phase indium oxide has more surface defects and higher chemical activity than the single stable cubic phase indium oxide, which helps to further improve the activity of gas-sensitive reactions. Metallic nickel is highly uniformly dispersed on the surface of indium oxide materials in the form of nanoclusters, which can effectively promote the catalytic conversion of NO2 molecules, accelerate the NO2 gas-sensitive reaction process, and improve the recovery speed of gas-sensitive response. The nanoclusters are extremely small in size, showing a higher surface-to-volume ratio and atomic activity, which can effectively reduce the inhibitory effect of the nickel component on the gas adsorption volume, promote the further improvement of the nickel catalytic activity, effectively reduce the kinetic barrier of the NO2 gas-sensitive reaction, and help to achieve transient, highly sensitive, and highly selective NO2 detection.
[0010] In some embodiments, the molar ratio of indium oxide to metallic nickel is 1:(0.001-0.2), which can be 1:(0.001-0.1), 1:(0.001-0.05), 1:(0.001-0.02), 1:(0.005-0.2), 1:(0.005-0.1), 1:(0.005-0.05), 1:(0.005-0.02), etc.
[0011] In some embodiments, the porous hollow core-shell microsphere structure has a diameter of 600-700 nm.
[0012] In some embodiments, the shell thickness is 45-55 nm.
[0013] In some embodiments, the core diameter is 350-450 nm.
[0014] In some embodiments, the nickel nanoclusters are 3-7 nm in size.
[0015] In a second aspect, a method for preparing a nickel nanocluster modified porous core-shell composite indium oxide material comprises the following steps:
[0016] Performing a first solvothermal reaction of indium salt and glycerol to obtain an indium glycerate precursor;
[0017] The indium glycerate precursor and the alkaline compound undergo a second solvothermal reaction to obtain an indium glycerate / indium oxyhydroxy precursor;
[0018] The indium glycerate / indium oxyhydroxide precursor is subjected to a first annealing treatment to obtain a porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide;
[0019] The porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide and nickel salt are uniformly mixed in a solution, and then the solid and liquid are separated, and the separated solid is subjected to a second annealing treatment under a mixed atmosphere to obtain a mixed atmosphere of an inert atmosphere and a reducing atmosphere.
[0020] The preparation method provided by the present invention can obtain the nickel nanocluster modified porous core-shell composite indium oxide material described in the first aspect of the present invention. Among them, the indium salt provides the required indium ions for the first solvothermal reaction synthesis, and the three hydroxyl groups in glycerol can react with the indium ions to cooperate and cross-link, resulting in the final synthesized precursor product being indium glycerate; the alkaline compound provides an alkaline atmosphere for the second solvothermal reaction, so that indium glycerate and hydroxide ions react to form an indium oxyhydroxide precursor under closed conditions, prompting the surface components of the indium glycerate precursor to react and diffuse outward and re-form an indium oxyhydroxide shell layer, and the remaining indium glycerate spheres form an inner core; indium oxyhydroxide and indium glycerate will form metastable rhombic corundum phase indium oxide and indium glycerate respectively during the first annealing process. Steady-state cubic indium oxide, thereby ensuring the synthesis of porous hollow core-shell cubic phase / rhombic corundum composite indium oxide; nickel salt provides nickel ions for material synthesis, which are fully stirred in the solution and exist in the porous hollow core-shell cubic phase / rhombic corundum composite indium oxide in the form of surface adsorption, and are further annealed into nickel nanoclusters in a reducing atmosphere. The nickel nanoclusters uniformly dispersed on the surface can avoid occupying a large number of active sites of indium oxide, and at the same time form a semiconductor-metal heterointerface between indium oxide and nickel nanoclusters, promote surface interface electron transfer, provide more reactive free electrons for NO2 gas-sensitive reaction, and help improve gas-sensitive performance.
[0021] The indium salt described in the present invention is a compound whose cation is an indium ion, such as one or more combinations of indium nitrate (In(NO3)3), indium chloride (InCl3) or indium sulfate (In2(SO4)3).
[0022] In some embodiments, the molar ratio of indium salt to glycerol is 1:(50-150).
[0023] The solvent thermal reaction described in the present invention is a reaction carried out under closed conditions, using liquid organic matter as a solvent, heating the reaction system to generate high pressure, wherein the "first" and "second" in the first solvent thermal reaction and the second solvent thermal reaction only represent different solvent thermal reaction processes. In some embodiments, the solvent used in the first solvent thermal reaction is isopropanol. The viscosity of the isopropanol solvent is higher than that of deionized water and lower than that of glycerol, which can ensure that the indium ions and glycerol are fully cross-linked and react while increasing the cross-linking reaction rate in the solvent thermal reaction.
[0024] In some embodiments, in the first solvothermal reaction, the reaction temperature is 100-200° C., and the reaction time is 1-12 h.
[0025] The alkaline compound described in the present invention is a compound that can make the pH of the aqueous solution greater than 7 when dissolved in water, such as one or more combinations of ammonia (NH3·H2O), urea (CH4N2O) or sodium hydroxide (NaOH).
[0026] In some embodiments, the solvent used in the second solvothermal reaction is anhydrous ethanol.
[0027] In some embodiments, the molar ratio of the indium glycerate precursor to the basic compound is 1:(50-200).
[0028] In some embodiments, in the second solvothermal reaction, the reaction temperature is 100-200° C., and the reaction time is 1-12 h.
[0029] In some embodiments, the first annealing treatment is performed at a temperature of 400-600° C. and for a time of 1-3 hours.
[0030] In some embodiments, the porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide is dispersed into a solution, and then nickel salt is added and stirred sufficiently to make the porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide and nickel salt uniformly mixed in the solution. Specifically, the solution is anhydrous ethanol.
[0031] The nickel salt described in the present invention is a compound whose cation is nickel ion, such as one or more combinations of nickel nitrate (Ni(NO3)2), nickel chloride (NiCl2) or nickel acetate (Ni(CH3COO)2).
[0032] In some embodiments, the molar ratio of porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide to nickel salt is 1:(0-0.02), which can be 1:(0.001-0.2), 1:(0.001-0.1), 1:(0.001-0.05), 1:(0.001-0.02), 1:(0.005-0.2), 1:(0.005-0.1), 1:(0.005-0.05), 1:(0.005-0.02), etc.
[0033] In some embodiments, the volume fraction of the reducing atmosphere in the mixed atmosphere is 8-12%. The reducing atmosphere can be formed by reducing gases such as hydrogen. The inert atmosphere can be formed by gases such as nitrogen, helium, argon, and xenon. During the second annealing treatment, the mixed gas is continuously introduced into the reaction system, and the flow rate of the mixed gas is 50-150 mL / min.
[0034] In some embodiments, the second annealing treatment is performed at a temperature of 100-300° C. and a time of 1-6 hours.
[0035] In a third aspect, a gas-sensitive element comprises a ceramic substrate and a gas-sensitive material, wherein the gas-sensitive material forms a sensing layer on the ceramic substrate, and the gas-sensitive material is the above-mentioned nickel nanocluster-modified porous core-shell composite indium oxide material.
[0036] The preparation method of the gas sensor is as follows: the gas sensitive material is mixed with deionized water and then ground evenly to form a slurry, the obtained slurry is evenly coated on a ceramic substrate, and then dried, and the coating and drying process is repeated several times, and then the slurry is completely dried.
[0037] In some embodiments, the mass ratio of the nickel nanocluster modified porous hollow core-shell heterogeneous indium oxide composite material to deionized water is 1:(2-6).
[0038] In some embodiments, the drying temperature of the ceramic substrate is 70-100° C., and the drying time is 2-6 min.
[0039] In some embodiments, the thorough drying temperature is 80-120° C. and the drying time is 8-24 h.
[0040] In a fourth aspect, a nickel nanocluster modified porous core-shell composite indium oxide material or gas sensor is used in detecting NO2.
[0041] The beneficial effects of the present invention are:
[0042] (1) The nickel nanocluster modified porous hollow core-shell composite material prepared by the present invention has a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide in the form of a micron-sphere, which is composed of a nanoparticle-assembled shell layer and a nanoparticle-assembled micron-sphere core body. The unique porous hollow core-shell structure design significantly increases the specific surface area of the material and provides abundant gas-sensitive reaction sites. The gaps between the porous nanoparticles and the core-shell layer provide a large number of diffusion channels for NO2, which can effectively improve the gas sensitivity and response recovery speed of the material.
[0043] (2) The nickel nanocluster modified porous hollow core-shell multiphase indium oxide composite material prepared by the present invention is prepared by regulating the solvothermal reaction of indium glycerate / indium oxyhydroxide precursor, and the porous hollow core-shell microsphere morphology is constructed while realizing the synthesis of a stable cubic phase / metastable rhombic corundum phase multiphase indium oxide matrix material. Compared with stable cubic phase indium oxide, metastable rhombic corundum phase indium oxide has more surface defects and higher chemical activity, which effectively increases the defect concentration of the matrix material, promotes NO2 adsorption and reaction, and optimizes the material's NO2 gas-sensitive reaction ability.
[0044] (3) Compared with traditional bulk / bulk nickel materials, the nickel nanoclusters modified porous hollow core-shell composite indium oxide composite material prepared by the present invention have extremely small sizes of nickel nanoclusters modified on the surface of indium oxide, and exhibit higher surface-to-volume ratio and atomic activity, which can effectively reduce the inhibitory effect of nickel components on gas adsorption volume. At the same time, it exhibits excellent catalytic conversion of NO2 molecules, which can effectively reduce the kinetic barrier of NO2 gas-sensitive reaction, and help to achieve transient, high-sensitivity and high-selectivity NO2 detection.
[0045] (4) The nickel nanocluster modified porous hollow core-shell composite indium oxide composite prepared by the present invention exhibits a transient response recovery speed (1 / 3s) and excellent NO2 response characteristics in the detection of NO2. The response value to 10ppm NO2 at 200°C can reach 454.62, and the detection limit of NO2 reaches 1ppb. At the same time, it can still show excellent selectivity in the detection of NO2, which can effectively avoid the gas-sensitive material being affected by other interfering gases in the detection of NO2. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0047] Figure 1The XRD patterns of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1-9 of the present invention; wherein, a is the XRD pattern of the cubic indium oxide and porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide materials prepared in Examples 1-5; b is the XRD pattern of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4, 6-9.
[0048] Figure 2 The present invention provides SEM images of porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 4, 6-9; wherein, a is a SEM image of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide material prepared in Example 4; b is a SEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 6; c is a SEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7; d is a SEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 8; e is a SEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 9.
[0049] Figure 3TEM, HRTEM and HAADF-STEM spectra of cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4 and 7 of the present invention; wherein a and b are TEM images of cubic indium oxide prepared in Example 1, and the inset in b is a selected area electron diffraction image; c is an HRTEM image of cubic indium oxide prepared in Example 1; d and e are regional images of measuring interplanar spacing values in c; f and g are TEM images of porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide prepared in Example 4, and the inset in g is a selected area electron diffraction image; h is a porous hollow core-shell prepared in Example 4. HRTEM image of cubic phase / rhombic corundum multiphase indium oxide; i and j are the regional diagrams of the measured interplanar spacing values in h; k and l are TEM images of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7, and the inset in l is the selected area electron diffraction image; m is the HRTEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7; n, o, p are the regional diagrams of the measured interplanar spacing values in m; q is the HAADF-STEM image of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7; r, s, t are the surface distribution maps of In, Ni and O elements respectively.
[0050] Figure 4 XPS spectra of cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide, and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4, 6-9 of the present invention; wherein a is In3 d is a fine spectrum; b is an O1s fine spectrum of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4, 6-9; c is a Ni2p fine spectrum of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 4, 7, 9.
[0051] Figure 5The BET-BJH spectra and specific surface area-pore volume distribution of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composites prepared in Examples 1, 4 and 7 of the present invention; wherein a is the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composites prepared in Examples 1, 4 and 7. a is the BET spectrum of the material; b is the BJH spectrum of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4 and 7; c is the specific surface area-pore volume distribution of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4 and 7.
[0052] Figure 6 NO2-TPD spectra of cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide, and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4, and 7 of the present invention.
[0053] Figure 7 The response values of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 4, 6-9 of the present invention to 10 ppm NO2 change at different operating temperatures.
[0054] Figure 8 The response values of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 4, 6-9 of the present invention to 10 ppm NO2 and 100 ppm other interfering gases at 200°C.
[0055] Fig. 9 This is the response recovery curve of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 of the present invention to 20-0.001ppm NO2 at 200°C; wherein, a is the response recovery curve of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 to 20-0.001ppm NO2 at 200°C; b is the response recovery curve of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 to 0.1-0.001ppm NO2 at 200°C.
[0056] Fig.10 This is the response recovery curve of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 of the present invention to 10 ppm NO2 at 200°C;
[0057] Fig.11 The response recovery cycle curve of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 of the present invention to 10 ppm NO2 at 200°C;
[0058] Fig.12 Schematic diagram of finite element simulation of cubic indium oxide and porous hollow core-shell cubic phase / rhombic corundum complex indium oxide materials prepared in Examples 1 and 4 of the present invention; wherein, a is the spatial concentration distribution diagram of NO2 after 10 ppm NO2 constant source diffusion for 5 s on the surface of cubic indium oxide prepared in Example 1; b is the spatial concentration distribution diagram of NO2 after 10 ppm NO2 constant source diffusion for 5 s on the surface of porous hollow core-shell cubic phase / rhombic corundum complex indium oxide prepared in Example 4.
[0059] Fig.13 This is a schematic diagram of the gas sensor prepared in Example 10 of the present invention. DETAILED DESCRIPTION
[0060] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0061] Example 1
[0062] A method for preparing a cubic indium oxide material comprises the following steps:
[0063] In(NO3)3 and glycerol were dissolved in 30 mL of isopropanol at a molar ratio of 1:135, mixed evenly, and then subjected to solvent thermal reaction at 180°C for 1 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor.
[0064] The prepared indium glycerate precursor was annealed at 400° C. for 1 h to obtain a cubic indium oxide material.
[0065] Example 2
[0066] A method for preparing a porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide material comprises the following steps:
[0067] InCl3 and glycerol were dissolved in 60 mL of isopropanol at a molar ratio of 1:50, mixed evenly, and then subjected to solvent thermal reaction at 100°C for 12 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor.
[0068] The prepared indium glycerate precursor was dissolved in 10 mL of anhydrous ethanol and uniformly dispersed, and NH3·H2O was added to the solution at a molar ratio of 1:100 to the indium glycerate precursor. After uniform dissolution, the solution was transferred to a closed condition and subjected to a solvothermal reaction at 160°C for 1 hour. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate / indium oxyhydroxide precursor.
[0069] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 600° C. for 1 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide material.
[0070] Example 3
[0071] A method for preparing a porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide material comprises the following steps:
[0072] In2(SO4)3 and glycerol were dissolved in 45 mL of isopropanol at a molar ratio of 1:150, mixed evenly, and then subjected to solvent thermal reaction at 120°C for 4 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor.
[0073] The prepared indium glycerate precursor was dissolved in 30 mL of anhydrous ethanol and uniformly dispersed, and CH4N2O was added to the solution at a molar ratio of 1:110 to the indium glycerate precursor. After uniform dissolution, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 200°C for 12 hours. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate / indium oxyhydroxide precursor.
[0074] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 450° C. for 3 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0075] Example 4
[0076] A method for preparing a porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide material comprises the following steps:
[0077] In(NO3)3 and glycerol were dissolved in 50 mL of isopropanol at a molar ratio of 1:120, mixed evenly, and then subjected to solvent thermal reaction at 160°C for 6 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor.
[0078] The prepared indium glycerate precursor was dissolved in 40 mL of anhydrous ethanol and uniformly dispersed, and NaOH was added to the solution at a molar ratio of 1:130 to the indium glycerate precursor. After uniform dissolution, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 180°C for 3 hours. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate / indium oxyhydroxide precursor.
[0079] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 500° C. for 1 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0080] Example 5
[0081] A method for preparing a porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide material comprises the following steps:
[0082] In(NO3)3 and glycerol were dissolved in 30 mL of isopropanol at a molar ratio of 1:160, mixed evenly, and then subjected to solvent thermal reaction at 120°C for 8 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor.
[0083] The prepared indium glycerate precursor was dissolved in 50 mL of anhydrous ethanol and uniformly dispersed, and CH4N2O was added to the solution at a molar ratio of 1:200 to the indium glycerate precursor. After uniform dissolution, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 120° C. for 12 hours. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate / indium oxyhydroxide precursor.
[0084] The prepared indium glycerate / indium hydroxide oxide precursor was annealed at 550° C. for 2 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0085] Example 6
[0086] A method for preparing a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material comprises the following steps:
[0087] InCl3 and glycerol were dissolved in 45 mL of isopropanol at a molar ratio of 1:110, mixed evenly, and then subjected to solvent thermal reaction at 100°C for 8 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor.
[0088] The prepared indium glycerate precursor was dissolved in 30 mL of anhydrous ethanol and uniformly dispersed, and NaOH was added to the solution at a molar ratio of 1:160 to the indium glycerate precursor. After uniform dissolution, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 130° C. for 6 h. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate / indium oxyhydroxide precursor.
[0089] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 450° C. for 1 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0090] The prepared porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide was dissolved in 30 mL of anhydrous ethanol solution and stirred thoroughly until uniformly dispersed, and then Ni(NO3)2 was added to the solution at a molar ratio of 1:0.005. After sufficient stirring, the solution was centrifuged, washed and dried, and then the prepared sample was annealed at 100°C in a 10% H2 / 90% N2 mixed gas at 50 mL / min for 1 h to obtain a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide composite material.
[0091] Example 7
[0092] A method for preparing a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material comprises the following steps:
[0093] In2(SO4)3 and glycerol were dissolved in 60 mL of isopropanol at a molar ratio of 1:60, mixed evenly, and then subjected to solvent thermal reaction at 190°C for 12 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor.
[0094] The prepared indium glycerate precursor was dissolved in 50 mL of anhydrous ethanol and uniformly dispersed, and CH4N2O was added to the solution at a molar ratio of 1:135 to the indium glycerate precursor. After uniform dissolution, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 100°C for 12 hours. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate / indium oxyhydroxide precursor.
[0095] The prepared indium glycerate / indium hydroxide oxide precursor was annealed at 600° C. for 2.5 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0096] The prepared porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide was dissolved in 35 mL of anhydrous ethanol solution and stirred thoroughly until uniformly dispersed, and then Ni(NO3)2 was added to the solution at a molar ratio of 1:0.01. After sufficient stirring, the solution was centrifuged, washed and dried, and then the prepared sample was annealed at 200°C in a 10% H2 / 90% N2 mixed gas at 120 mL / min for 2 h to obtain a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide composite material.
[0097] Example 8
[0098] A method for preparing a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material comprises the following steps:
[0099] In(NO3)3 and glycerol were dissolved in 30 mL of isopropanol at a molar ratio of 1:50, mixed evenly, and then subjected to solvent thermal reaction at 160°C for 2 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor.
[0100] The prepared indium glycerate precursor was dissolved in 40 mL of anhydrous ethanol and uniformly dispersed, and NH3·H2O was added to the solution at a molar ratio of 1:150 to the indium glycerate precursor. After uniform dissolution, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 200°C for 1 hour. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate / indium oxyhydroxide precursor.
[0101] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 550° C. for 1 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite indium oxide material.
[0102] The prepared porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide was dissolved in 60 mL of anhydrous ethanol solution and stirred thoroughly until uniformly dispersed, and then Ni(CH3COO)2 was added to the solution at a molar ratio of 1:0.015. After sufficient stirring, the solution was centrifuged, washed and dried, and then the prepared sample was annealed at 180°C for 3 h in a 150 mL / min 10% H2 / 90% N2 mixed gas to obtain a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide composite material.
[0103] Example 9
[0104] A method for preparing a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material comprises the following steps:
[0105] InCl3 and glycerol were dissolved in 60 mL of isopropanol at a molar ratio of 1:150, mixed evenly, and then subjected to solvent thermal reaction at 200°C for 4 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate precursor.
[0106] The prepared indium glycerate precursor was dissolved in 55 mL of anhydrous ethanol and uniformly dispersed, and CH4N2O was added to the solution at a molar ratio of 1:200 to the indium glycerate precursor. After uniform dissolution, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 140°C for 12 hours. The reaction product was centrifuged, washed, and dried to obtain an indium glycerate / indium oxyhydroxide precursor.
[0107] The prepared indium glycerate / indium hydroxy oxide precursor was annealed at 600° C. for 1 h to obtain a porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide material.
[0108] The prepared porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide was dissolved in 50 mL of anhydrous ethanol solution and stirred thoroughly until uniformly dispersed, and then NiCl2 was added to the solution at a molar ratio of 1:0.02. After sufficient stirring, the solution was centrifuged, washed and dried, and then the prepared sample was annealed at 300°C in a 120 mL / min 10% H2 / 90% N2 mixed gas for 1 h to obtain a nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide composite material.
[0109] Example 10
[0110] A gas sensor and a preparation method thereof, the gas sensor comprising a ceramic substrate, a platinum wire, a gas sensing material and a gold electrode, the preparation method specifically comprising the following steps:
[0111] The cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide composite materials prepared in Examples 1-9 were mixed with deionized water in a mass ratio of 1:5 and ground evenly to form a slurry. The resulting slurry was then evenly coated on a ceramic substrate, and the ceramic substrate was placed in an oven at 80°C and dried for 5 minutes before being taken out. After repeating the coating and drying process five times, the ceramic substrate coated with the gas-sensitive material was placed in an oven at 100°C and dried for 12 hours, and a platinum wire was connected to obtain a gas-sensitive element.
[0112] Performance Testing:
[0113] Figure 1 The cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1-9 of the present invention; Figure 1 It can be obtained that the material prepared in Example 1 exhibits a pure cubic phase structure, proving that the indium glycerate precursor can be completely transformed into cubic indium oxide after annealing, and the indium glycerate precursor can obtain a cubic phase / rhombic corundum multiphase indium oxide material after further solvent thermal reaction and annealing under alkaline conditions, and the diffraction peak intensity related to the rhombic corundum phase will increase with the increase of the alkali source concentration; from Figure 1 It can be observed in b that the nickel nanoclusters modified on the surface of the cubic phase / rhombic corundum complex phase indium oxide material will not destroy the original cubic phase / rhombic corundum complex phase crystal structure; no obvious nickel-related diffraction peaks were observed in the XRD spectra of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide composite materials prepared in Examples 6-9, proving that the nickel content is low and highly dispersed on the surface of the cubic phase / rhombic corundum complex phase indium oxide composite materials.
[0114] Figure 2The SEM images of the porous hollow core-shell cubic phase / rhombic corundum complex indium oxide and the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex indium oxide composite materials prepared in Examples 4 and 6-9 of the present invention; it can be seen that the porous hollow core-shell cubic phase / rhombic corundum complex indium oxide and the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum complex indium oxide composite materials prepared in Examples 4 and 6-9 all exhibit typical micron-spherical structures, with a diameter of about 600 nm, and the micron-spheres are further formed by the accumulation of a large number of nanoparticles. At the same time, no obvious nickel-related structures are observed on the surface, which proves that the nickel nanoclusters are highly dispersedly grown on the surface of the cubic phase / rhombic corundum complex indium oxide matrix.
[0115] Figure 3 TEM, HRTEM and HAADF-STEM spectra of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4 and 7 of the present invention; Figure 3 a and Figure 3 In b, it can be observed that the cubic indium oxide material has a micron-spherical morphology with a diameter of about 600nm, and is further composed of nanoparticles. The characteristic diffraction rings of cubic indium oxide are calibrated in the selected area electron diffraction. In addition, Figure 3 The interplanar spacings marked in regions d and e in c correspond to the (211) and (222) planes of cubic indium oxide, respectively, proving that the synthesized material is cubic indium oxide. Figure 3 f and Figure 3 g, it can be observed that the cubic phase / rhombic corundum multiphase indium oxide composite material exhibits a porous hollow core-shell microsphere morphology, in which the outer sphere diameter is about 660nm, the shell thickness is about 50nm, the inner sphere core diameter is about 400nm, and it is further stacked by nanoparticles. The characteristic diffraction rings of cubic phase indium oxide and rhombic corundum phase indium oxide are calibrated in the selected area electron diffraction. In addition, Figure 3 The interplanar spacings marked in regions i and j in h correspond to the (400) crystal plane of cubic indium oxide and the (104) crystal plane of rhombic corundum phase indium oxide, respectively, proving that the synthesized material is a cubic phase / rhombic corundum multiphase indium oxide composite material. Figure 3 k and Figure 3 It can be observed in Figure 1 that the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material still exhibits a porous hollow core-shell microsphere morphology, in which the outer sphere diameter, sphere shell thickness, and inner sphere core diameter are close to those of the cubic phase / rhombic corundum multiphase indium oxide composite material, and are further stacked by nanoparticles. The characteristic diffraction rings of cubic phase indium oxide and rhombic corundum phase indium oxide and the diffraction spots of nickel are simultaneously calibrated in the selected area electron diffraction. In addition, Figure 3The interplanar spacings marked in the n, o, and p regions in m correspond to the (211) crystal plane of cubic indium oxide, the (110) crystal plane of rhombic corundum phase indium oxide, and the (012) crystal plane of nickel, respectively, proving that the synthesized material is a nickel nanocluster-modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material. Figure 3 The HAADF-STEM image and element distribution diagram of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material modified by nickel nanoclusters in qt show the uniform distribution of In, O, and Ni, proving that the prepared material contains the above elements, among which the Ni signal is weak and evenly distributed, proving that the nickel nanoclusters are highly evenly dispersed and loaded on the surface of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material.
[0116] Figure 4 XPS spectra of cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide, and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4, 6-9 of the present invention; wherein, from Figure 4 It can be seen from a that the In ions in the sample all appear in the valence states of +2 and +3. The generation of +2-valence In ions indicates that the synthesized material contains a large number of positively charged structural defects, and the material structure compensates for the electrical neutrality and causes the In ions to transform to a low-valence state. Figure 4 As can be seen from b, all samples contain adsorbed oxygen, oxygen vacancies and lattice oxygen components. After surface modification with nickel nanoclusters, the lattice oxygen component in the material increased significantly while the chemically adsorbed oxygen ratio decreased significantly, proving that nickel nanoclusters can inhibit the generation of surface chemically adsorbed oxygen. Since both oxygen and NO2 exhibit electron-withdrawing properties, a high content of chemically adsorbed oxygen on the surface of the material will consume more free electrons, thereby inhibiting the reaction ability of NO2 with free electrons in the conduction band of the material, and further inhibiting the sensitivity of the material to NO2. That is, the modification of nickel nanoclusters will promote the gas-sensitive reaction between NO2 and the material; Figure 4 c It can be seen that there is no Ni signal in the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide prepared in Example 4, and the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 shows Ni 3+ The nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 4 showed signals of both metallic Ni and Ni-Ni bonds, proving that excessive addition of nickel source will cause spontaneous agglomeration of nickel nanoclusters, thereby inhibiting its surface-to-volume ratio and chemical activity, and further inhibiting its gas-sensing performance.
[0117] Figure 5The BET-BJH spectra and specific surface area-pore volume distribution of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4 and 7 of the present invention; the specific surface areas of the cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials are calculated to be 35.46, 65.58 and 54.03 m 2 g -1 , the pore volumes are 0.00575, 0.01158 and 0.01175 cm 3 g -1 nm -1 It shows that the construction of porous hollow core-shell cubic phase / rhombic corundum composite indium oxide morphology will significantly increase the specific surface area and porosity of the material, increase the number of gas-sensitive reaction sites and gas diffusion channels, and promote the improvement of the sensitivity and response recovery speed of NO2 gas-sensitive reaction; while nickel nanocluster modification will not have a significant effect on the specific surface area and porosity of the material, that is, nickel nanocluster modification will not significantly inhibit the gas-sensitive performance.
[0118] Figure 6 NO2-TPD spectra of cubic indium oxide, porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 1, 4 and 7 of the present invention. It can be clearly seen that the NO2 desorption peak intensity of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material modified by nickel nanocluster is the highest, while the cubic phase indium oxide intensity is the lowest, indicating that the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide morphology and phase structure design and the surface modification of nickel nanocluster will promote the adsorption of NO2, and nickel nanocluster will significantly increase the adsorption amount of NO2, indicating that the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material can show a better NO2 gas-sensitive response ability.
[0119] Figure 7The porous hollow core-shell cubic phase / diamond corundum complex phase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / diamond corundum complex phase indium oxide composite materials prepared in Examples 4, 6-9 of the present invention change the response value of 10ppm NO2 at different working temperatures. It can be seen that the samples all show the best NO2 response value at 200°C, and the NO2 response value of the porous hollow core-shell cubic phase / diamond corundum complex phase indium oxide composite materials modified by nickel nanocluster is higher than that of the porous hollow core-shell cubic phase / diamond corundum complex phase indium oxide, proving that nickel nanocluster can effectively improve the gas-sensitive performance of the material to NO2; in addition, the nickel nanocluster modified porous hollow core-shell cubic phase / diamond corundum complex phase indium oxide composite material prepared in Example 7 can reach a response value of 454.92 to 10ppm, showing excellent NO2 gas-sensitive performance.
[0120] Figure 8 The response values of the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials prepared in Examples 4, 6-9 of the present invention to 10ppm NO2 and 100ppm other interfering gases at 200°C. It can be seen that the sensitivity of the material to NO2 is much higher than that to other interfering gases, proving that the porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide and the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite materials both exhibit excellent NO2 gas-sensitive selectivity.
[0121] Fig. 9 The response recovery curve of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 of the present invention to 20-0.001ppm NO2 at 200°C; it can be seen that the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material shows an obvious response value and a faster response recovery speed to 20-0.001ppm NO2, proving that the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material can achieve quantitative, rapid and high-precision detection of NO2 in a wide concentration range.
[0122] Fig.10 The response recovery curve of the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material prepared in Example 7 of the present invention to 10ppm NO2 at 200°C shows that the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material shows excellent sensitivity to 10ppm NO2, and the recorded response and recovery times are 1s and 3s, respectively, indicating that the nickel nanocluster modified porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide composite material can achieve high-sensitivity transient detection of NO2 gas.
[0123] Fig.11 The present invention is a method for detecting 10 ppm NO2 by using nickel nanocluster-modified porous hollow core-shell cubic phase / diamond-shaped corundum multiphase indium oxide composite material at 200°C. The image shows that in five consecutive tests, the response value and response recovery speed of the nickel nanocluster-modified porous hollow core-shell cubic phase / diamond-shaped corundum multiphase indium oxide composite material are almost unaffected by the ambient humidity. The material can complete 10 consecutive and complete NO2 response recovery processes within 600 seconds, which proves that the nickel nanocluster-modified porous hollow core-shell cubic phase / diamond-shaped corundum multiphase indium oxide composite material has fast, stable and accurate NO2 gas recognition capability.
[0124] Fig.12 Schematic diagram of finite element simulation of cubic indium oxide and porous hollow core-shell cubic phase / rhombic corundum multiphase indium oxide materials prepared in Examples 1 and 4 of the present invention, according to Figure 2 , Figure 3 , Figure 5 A finite element model was constructed based on the results in the experiment. A constant source concentration field of 10 ppm was applied to the outer surface of the model, and the spatial concentration distribution of NO2 was recorded 5 seconds after the start of the diffusion process. The results showed that for cubic indium oxide, due to its low specific surface area and porosity, it was difficult for NO2 gas to quickly diffuse into the interior of the micron-sphere structure, so the concentration in the internal area was low. For the porous hollow core-shell cubic phase / rhombus corundum composite indium oxide material, the finite element simulation results showed that the NO2 concentration in the hollow structure part of the porous hollow core-shell layer was higher, indicating that its unique porous hollow core-shell structure design can effectively promote the diffusion of NO2 molecules into the interior of the material and promote more NO2 molecules to quickly contact with the gas-sensitive reaction sites, thereby achieving the comprehensive gas-sensitive performance improvement of the material to NO2 response value and response recovery speed.
[0125] Fig.13 The schematic diagram of the gas sensor prepared in Example 10 of the present invention includes a ceramic substrate, a gold electrode, four platinum wires and a sensing material. In the preparation process of the gas sensor, the prepared gas-sensitive material is coated on the ceramic substrate, and after uniform coating and drying, the ceramic substrate is welded to the four corner bases through four platinum wires to obtain the gas sensor.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A nickel nanocluster modified porous core-shell composite indium oxide material, characterized in that: Comprising indium oxide and metallic nickel, wherein the molar ratio of indium oxide to metallic nickel is 1:(0-0.2); The crystal phase of the indium oxide is a composite phase composed of a cubic phase and a rhombic corundum phase, and the structure of the indium oxide is a porous hollow core-shell micron-spherical structure, which is composed of a shell layer wrapping a core, and a hollow cavity is formed between the shell layer and the core, wherein the shell layer is composed of porous indium oxide nanoparticles, and the core is a micron-sphere assembled from porous indium oxide nanoparticles; Metallic nickel is dispersed in the form of nanoclusters on the surface of the porous hollow core-shell micron-spherical structure.
2. The nickel nanocluster modified porous core-shell composite indium oxide material according to claim 1, characterized in that: The molar ratio of indium oxide to metallic nickel is 1:(0.001-0.2).
3. The nickel nanocluster modified porous core-shell composite indium oxide material as claimed in claim 2, characterized in that: The molar ratio of indium oxide to metallic nickel is 1:(0.001-0.1).
4. The nickel nanocluster modified porous core-shell composite indium oxide material according to claim 2, characterized in that: The molar ratio of indium oxide to metallic nickel is 1:(0.001-0.05).
5. The nickel nanocluster modified porous core-shell composite indium oxide material as claimed in claim 2, characterized in that: The molar ratio of indium oxide to metallic nickel is 1:(0.001-0.02).
6. The nickel nanocluster modified porous core-shell composite indium oxide material according to claim 2, characterized in that: The molar ratio of indium oxide to metallic nickel is 1:(0.005-0.2).
7. The nickel nanocluster modified porous core-shell composite indium oxide material according to claim 2, characterized in that: The molar ratio of indium oxide to metallic nickel is 1:(0.005-0.1).
8. The nickel nanocluster modified porous core-shell composite indium oxide material according to claim 2, characterized in that: The molar ratio of indium oxide to metallic nickel is 1:(0.005-0.05).
9. The nickel nanocluster modified porous core-shell composite indium oxide material according to claim 2, characterized in that: The molar ratio of indium oxide to metallic nickel is 1:(0.005-0.02).
10. The nickel nanocluster modified porous core-shell composite indium oxide material according to claim 1, characterized in that: The diameter of the porous hollow core-shell microsphere structure is 600-700 nm; or, shell thickness is 45-55 nm; or, core diameter is 350-450 nm; Alternatively, the size of nickel nanoclusters is 3-7 nm.
11. A method for preparing a nickel nanocluster modified porous core-shell composite indium oxide material, characterized in that: The steps include: Performing a first solvothermal reaction of indium salt and glycerol to obtain an indium glycerate precursor; The indium glycerate precursor and the alkaline compound undergo a second solvothermal reaction to obtain an indium glycerate / indium oxyhydroxy precursor; The indium glycerate / indium oxyhydroxide precursor is subjected to a first annealing treatment to obtain a porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide; The porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide and nickel salt are uniformly mixed in a solution, and then the solid and liquid are separated, and the separated solid is subjected to a second annealing treatment under a mixed atmosphere to obtain a mixed atmosphere of an inert atmosphere and a reducing atmosphere.
12. The preparation method according to claim 11, characterized in that: The molar ratio of indium salt to propylene glycol is 1:(50-150); Or, the solvent used in the first solvothermal reaction is isopropanol; Alternatively, in the first solvothermal reaction, the reaction temperature is 100-200°C, and the reaction time is 1-12 h.
13. The preparation method according to claim 11, characterized in that: The solvent used in the second solvothermal reaction is anhydrous ethanol; Or, the molar ratio of the indium glycerate precursor to the alkaline compound is 1:(50-200); Or, in the second solvothermal reaction, the reaction temperature is 100-200 °C, and the reaction time is 1-12 h; Alternatively, the first annealing treatment is performed at a temperature of 400-600° C. and a annealing time of 1-3 h.
14. The preparation method according to claim 11, characterized in that: The porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide is dispersed into the solution, and then nickel salt is added and stirred sufficiently to make the porous hollow core-shell cubic phase / rhombic corundum complex phase indium oxide and the nickel salt evenly mixed in the solution.
15. The preparation method according to claim 11, characterized in that: The molar ratio of indium oxide to nickel salt in the porous hollow core-shell cubic phase / rhombic corundum composite phase is 1:(0-0.02).
16. The preparation method according to claim 15, characterized in that: The molar ratio of indium oxide to nickel salt in the porous hollow core-shell cubic phase / rhombic corundum composite phase is 1:(0.001-0.2).
17. The preparation method according to claim 15, characterized in that: The molar ratio of indium oxide to nickel salt in the porous hollow core-shell cubic phase / rhombic corundum composite phase is 1:(0.001-0.1).
18. The preparation method according to claim 15, characterized in that: The molar ratio of indium oxide to nickel salt in the porous hollow core-shell cubic phase / rhombic corundum composite phase is 1:(0.001-0.05).
19. The preparation method according to claim 15, characterized in that: The molar ratio of indium oxide to nickel salt in the porous hollow core-shell cubic phase / rhombic corundum composite phase is 1:(0.001-0.02).
20. The preparation method according to claim 15, characterized in that: The molar ratio of porous hollow core-shell cubic phase / rhombic corundum composite phase indium oxide to nickel salt is 1:(0.005-0.2).
21. The preparation method according to claim 15, characterized in that: The molar ratio of indium oxide to nickel salt in the porous hollow core-shell cubic phase / rhombic corundum composite phase is 1:(0.005-0.1).
22. The preparation method according to claim 15, characterized in that: The molar ratio of indium oxide to nickel salt in the porous hollow core-shell cubic phase / rhombic corundum composite phase is 1:(0.005-0.05).
23. The preparation method according to claim 15, characterized in that: The molar ratio of indium oxide to nickel salt in the porous hollow core-shell cubic phase / rhombic corundum composite phase is 1:(0.005-0.02).
24. The preparation method according to claim 11, characterized in that: In the mixed atmosphere, the volume fraction of reducing atmosphere is 8~12%; Alternatively, the second annealing treatment is performed at a temperature of 100-300° C. and a annealing time of 1-6 h.
25. A gas sensor, comprising a ceramic substrate and a gas-sensitive material, wherein the gas-sensitive material forms a sensing layer on the ceramic substrate, wherein: The gas-sensitive material is the nickel nanocluster-modified porous core-shell composite indium oxide material described in any one of claims 1 to 10 or the nickel nanocluster-modified porous core-shell composite indium oxide material obtained by the preparation method described in any one of claims 11 to 24.
26. Use of the nickel nanocluster modified porous core-shell complex indium oxide material described in any one of claims 1 to 10, or the nickel nanocluster modified porous core-shell complex indium oxide material obtained by the preparation method described in any one of claims 11 to 24, or the gas sensor described in claim 25 in detecting NO2.
Citation Information
Patent Citations
Reduced graphene oxide coated platinum / stannic oxide nano-particle cluster gas sensor and preparation method thereof
CN108318510A
Gas sensor based on p-n heterojunction structure NiO-In2O3 composite nanosphere
CN109632893A